DETERMINATION OF CARBAMATE PESTICIDES USING A BIOSENSOR BASED ON ENZYME ACETYLCHOLINESTERASE AND CHOLIN OXIDASE ON PLATINUM ELECTRODE - Mashuni Mashuni; M. Syahrul; A. Ahmad; A. W. Wahab (Indonesian Journal of Chemistry, 2010)
In recent years, instead of their potential hazard to human health, carbamic pesticides are widely used in agriculture. Therefore, there is a growing interest in rapid and accurate determination for food safety and environmental monitoring. The aim of this research is to designs a biosensor for analyzing carbamate pesticides residue in sample with composite variables of glutaraldehyde (GA) concentration in electrode membrane. Enzyme acetylcholinesterase (AChE) was co-immobilised with choline oxidase (ChO) onto a platinum (Pt) surface using a solution of 5%, 10%, 15% cellulose acetate and 25% glutaraldehyde. The result of this research show that detection limit of the sensor using cellulose acetate 5%, 10 % and 15 % are 10-7.7 M, 10-8.7 M and 10-7.6 M respectively. The results are approximately equal to 2.2 ppb-0.2 ppb, which means that this biosensor is very sensitive for determining carbamates pesticides residue. Detection limit of biosensors are comparable to that of the conventional instrument such as Gas Chromatography (GC) and High Pressure Liquid Chromatography (HPLC), i.e. 1.5 ppb and 2.0 ppb respectively. The proposed electrochemical pesticide sensitivity test exhibited high sensitivity, desirable accuracy, low cost and simplified procedure.